Close Reading: Making Sense in Robert Frost’s Stopping by Woods on a Snowy Evening - Budhathoki, Mahendra Kumar (Kanya Journal, 2022)
Close reading opens the way to comprehend a text critically, which provides surface and underlying meanings. It systematises a thoughtful reading with social interaction based on textual evidences and concludes to a proposition and argumentation. It enables the reader to observe the text and contextualize the meanings and ideas derived from it in the practical sphere of life as well. College students study to learn reading strategies and skills. The purpose of this paper is to present a sample of close reading in Robert Frost’s poem, “Stopping by Woods on a Snowy Evening.” This paper has used qualitative descriptive method to qualify the essence of close reading in the poem. This research paper has described the stages of close reading to unravel the general understanding and underlying pattern of Frost’s poem. This paper becomes more useful to teachers and advanced readers to read literary and non-literary texts effectively. The activities discussed in this paper stimulate them to read other texts closely. It broadens the horizon of understanding after dealing with very careful and precise details that evoke the insights of knowledge. This dynamics of reading, in this way, enriches the critical faculty of readers.